2020
DOI: 10.3389/fnins.2020.00168
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Near-Infrared Spectroscopy-Based Brain-Computer Interface Using Regularized Linear Discriminant Analysis Ensemble Classifier Based on Bootstrap Aggregating

Abstract: Ensemble classifiers have been proven to result in better classification accuracy than that of a single strong learner in many machine learning studies. Although many studies on electroencephalography-brain-computer interface (BCI) used ensemble classifiers to enhance the BCI performance, ensemble classifiers have hardly been employed for near-infrared spectroscopy (NIRS)-BCIs. In addition, since there has not been any systematic and comparative study, the efficacy of ensemble classifiers for NIRS-BCIs remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Recently, Shin and Im (2020) demonstrated that ensemble of weak classifiers resulted in a better classification accuracy than that of a single strong classifier. Based on this work, the ensemble of regularized LDA based on bootstrap aggregating (Bagging) algorithm was employed to validate the performance of subjectindependent fNIRS-based BCI.…”
Section: Ensemble Of Regularized Ldamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shin and Im (2020) demonstrated that ensemble of weak classifiers resulted in a better classification accuracy than that of a single strong classifier. Based on this work, the ensemble of regularized LDA based on bootstrap aggregating (Bagging) algorithm was employed to validate the performance of subjectindependent fNIRS-based BCI.…”
Section: Ensemble Of Regularized Ldamentioning
confidence: 99%
“…In this study, the ensemble classifier was implemented using the MATLAB "fitcensemble" function. According to the previous study (Shin and Im, 2020), the number of weak classifiers, fraction of training set to resample, and gamma value for regularized LDA were set to 50, 100%, and 0.1, respectively.…”
Section: Ensemble Of Regularized Ldamentioning
confidence: 99%
“…First, from the algorithm perspective, most studies were concerned with classification issues in the field of EEG analysis (e.g., [230][231][232][233][234]), for example, human mental emotion classification [230], classification of forearm movement imagery [231], detection of acute pain signals [232], sleep stage classification [235], classification of individuals into a normal group and one with particular diseases [236], and classification of repeating stimuli as either old or new [237]. Furthermore, ensemble classifiers are more effective than a single strong learner [238]. Thus, it is suggested that scholars should Second, machine learning and deep learning have been widely applied to EEG data analysis, particularly CNNs (e.g., [239][240][241][242][243][244][245]).…”
Section: Latest Research Concerning Ai-enhanced Eeg Analysismentioning
confidence: 99%
“…Ensemble methods for NIRS data improve machine learning performance through the combination of several weak learners. 40 Decision tree classification randomly samples the input data (i.e., bootstrapping) and tests the out-of-bag samples. This randomization process decorrelates individual decision trees to prevent overfitting.…”
Section: Decision Tree Classificationmentioning
confidence: 99%